Mechanical System Design for a Handling System Demonstrator for Simulating Real Production Environments - Ismadi, Ignatius Henry; Saputra, Tri Hannanto; Widyatmoko, Ratmono Hari; Prasetyo, Andi; Wijaya, Dikky Kusuma; Supriyono, Romi; Praba, Alto Gandhang (STMIK Widya Cipta Dharma, 2025)
The paradigm shift in manufacturing towards Industry 4.0 requires the availability of vocational education infrastructure that is capable of representing actual production floor conditions. The material handling system is a vital component in the integration of the industrial supply chain, which involves precise synchronization between mechanical design and control systems. However, the educational tools currently available often fail to simulate the complexity of this integration due to designs that are too simple or not industry standard. This study aims to design and realize a mechanical system in a material handling system simulator by adopting the Learning Factory concept. The research was conducted using the Research and Development (R&D) method with the ADDIE approach. The main focus of the research was the design of a modular mechanical structure using aluminum profiles, conveyor transmission mechanisms, and an integrated electro-pneumatic control system. The design results were validated through the realization of physical prototypes and functional testing. The research results show that the developed mechanical design has high rigidity and is capable of simulating the material transportation process with stability. The designed control system successfully integrated inductive and optical sensors and pneumatic actuators with 100% sorting logic accuracy. This simulator provides a realistic platform for students to learn about the interaction between mechanical and control components in a safe but authentic production environment.